Excavation of irrigation canal changes the cropping pattern in 2013-14: Auria Union, Narail, Bangladesh - Hasan, Md Amit; Rahman, Md Shamsur; Rahman, Md Atiqur; Biswas, Shaswata; Bhattacharjee, Rimi; Shaikah, Md Maruf (Asian Journal of Medical and Biological Research, 2016)
The principal crop during winter is Bororice and it occupies about 70% of crops. Being a country of 140 million inhabitants, agriculture is still the major water using sector in order to feed a growing population where at least 40 million people do not have a square meal. Recently, Bangladesh Water Development Board (BWDB) launched some projects to various water user groups for maintenance and expenditure recovery. Chenchuri Irrigation Sub Project is under South-West Area Integrated Water Resources Planning and Management Project (SWAIWRPMP). The project area covers the South Western Narail District along with Auria Union at Narail Sadar Upazila. Data were collected from 150 farmers of 6 villages in Auria Union. This research investigates the overall cropping pattern in Auria Union, Narail Sadar Upazila, before the construction of canal (during 1987-88), after the construction of canal (during 2009-10)and after re-excavation of canal (2012-13). The result showed that, before the construction of canal (during 1987-88) there were 5 types of cropping pattern and after the construction of canal (during 2009-10) there were 6 types of cropping pattern. But after re-excavation of canal (2012-13), 12 types of cropping pattern were recorded. Among them, the T. Aman and Boro were the most prominent cropping pattern. In Kharif 1, Kharif 2 and Rabi seasons, various types of crops were cultivated. Such as Aus, B. Aman, T. Aman, Boro, Jute, Sesame, Summer vegetables, Chilly, Garlic, Chickpea, Lentil, Mustard, Onion, Sugarcane, Turmeric, Wheat, Winter vegetables etc. The result revealed that, the re-excavation of canal have significantly positive impact on the Boro, Wheat, Turmeric, Chilly, Chick pea, Sugarcane, Lentil production. The Boro rice cultivation increased significantly day by day and it replaced other crops gradually. Because, farmers get irrigation water easily and cheaply from canal in Rabi season (16 October - 15 March). The present study showed that, the excavation of irrigation canal completely changes the cropping pattern at auriaunion in Narail, Bangladesh. Asian J. Med. Biol. Res. June 2016, 2(2): 285-296